A qualitative study on elderly depression and their help seeking behaviour in Kelantan - Sanggar, Arunah A/P (2018)
Despite a high prevalence of elderly depression in Malaysia, professional help seeking is limited. This study aims to explore the expression of emotional distress among elderly in Kelantan, their help seeking behaviour and their knowledge on the availability of professional help. Qualitative interpretative phenomenological approach with face to face interviews were conducted in 19 Malay elderly who have been screened positive for depression. The emotional distress in the elderly emerged as ‘Life is Miserable’, ‘Depression is a Sign of Weakness’ and ‘My Destiny is Predetermined’. The emerging themes for help seeking behaviours are ‘Self Efficacy’, ‘Social Support Network’ and ‘Formal Non Mental Health Professionals’. All of the participants had no knowledge on the availability of professionals mental health services and claimed neither would they require these services despite being screened positive for depression. Therefore there is a need to improve mental health literacy among the elderly about depression and empower their social supports.